Comprehensive metabolic profiling of Alismatis Rhizoma triterpenes in rats based on characteristic ions and a triterpene database - Lu Wang; Sen Li; Jiaxin Li; Zhongzhe Cheng; Yulin Feng; Hui Ouyang; Zhifeng Du; Hongliang Jiang (Elsevier, 2021)
Alismatis Rhizoma (AR) is widely used in Chinese medicine, and its major bioactive components, triterpenes, reportedly possess various pharmacological activities. Therefore, it is very important to study the metabolism of triterpenes in vivo. However, the metabolism of AR triterpene extract has not been comprehensively elucidated due to its complex chemical components and metabolic pathways. In this study, an ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry method, which was based on the characteristic ions from an established database of known triterpenes, was used to analyze the major metabolites in rats following the oral administration of Alismatis Rhizoma extracts (ARE). As a result, a total of 233 constituents, with 85 prototype compounds and 148 metabolites, were identified for the first time. Hydrogenation, oxidation, sulfate and glucuronidation conjugation were the major metabolic pathways for triterpenes in AR. In addition, the mutual in vivo transformation of known ARE triterpenes was discovered and confirmed for the first time. Those results provide comprehensive insights into the metabolism of AR in vivo, which will be useful for future studies on its pharmacodynamics and pharmacokinetics. Moreover, this established strategy may be useful in metabolic studies of similar compounds.